Distribution Center Location Selection using an Extension of Fuzzy TOPSIS Approach - Tuan Nguyen Anh; Hien Hoang Thi (International Journal of Supply Chain Management, 2017)
Distribution center location is a very important problem in practice. This paper proposes a generalized fuzzy TOPSIS approach to support for distribution center location selection process. In the proposed approach, the ratings of alternatives and importance weights of criteria for distribution center location selection are represented by generalized triangular fuzzy numbers. Then, the membership functions of the final fuzzy evaluation value in the proposed approach are developed based on the linguistic expressions. Finally, this study applies the proposed generalized fuzzy TOPSIS to a real case of distribution center location selection in a company demonstrating its advantages and applicability.